Novel expansion techniques for skin grafts - Dinesh Kadam (Indian Journal of Plastic Surgery)
The quest for skin expansion is not restricted to cover a large area alone, but to produce acceptable uniform surfaces, robust engraftment to withstand mechanical shear and infection, with a minimal donor morbidity. Ease of the technique, shorter healing period and reproducible results are essential parameters to adopt novel techniques. Significant advances seen in four fronts of autologous grafting are: (1) Dermal–epidermal graft expansion techniques, (2) epidermal graft harvests technique, (3) melanocyte-rich basal cell therapy for vitiligo and (4) robust and faster autologous cell cultures. Meek's original concept that the sum of perimeter of smaller grafts is larger than the harvested graft, and smaller the graft size, the greater is the potential for regeneration is witnessed in newer modification. Further, as graft size becomes smaller or minced, these micrografts can survive on the wound bed exudate irrespective of their dermal orientation. Expansion produced by 4 mm × 4 mm sized Meek micrografts is 10-folds, similarly 0.8 mm × 0.8 mm size micrografts produce 100-fold expansion, which becomes 700-fold with pixel grafts of 0.3 mm × 0.3 mm size. Fractional skin harvest is another new technique with 700 μ size full thickness graft. These provide instant autologous non-cultured graft to cover extensive areas with similar quality of engraftment surface as split skin grafts. Newer tools for epidermal blister graft harvest quickly, with uniform size to produce 7-fold expansions with reproducible results. In addition, donor area heals faster with minimal scar. Melanocyte-rich cell suspension is utilised in vitiligo surgery tapping the potential of hair root melanocytes. Further advances in the cell culture to reduce the cultivation time and provide stronger epidermal sheets with dermal carrier are seen in trials.